Respiratory syncytial virus-neutralizing serum antibody titers in infants following palivizumab prophylaxis with an abbreviated dosing regimen - Claydon, Jennifer (PLoS One, 2017)
BACKGROUND: Monthly injections of palivizumab during the respiratory syncytial virus (RSV) season in at-risk infants reduces RSV-associated hospitalizations. However, the additive effect of naturally acquired immunity remains unclear. The objective of this study was to assess total neutralizing serum antibodies (NAb) against RSV in at-risk infants who had received an abbreviated course of palivizumab prophylaxis. METHODS: Serum samples were collected from infants enrolled in the RSV Immunoprophylaxis Program in British Columbia, Canada over 2 consecutive RSV seasons (2013 to 2015). Infants in this program had received an abbreviated course of palivizumab in accordance with the provincial guidelines. Data were compared to adults and infants less than 12 months of age who did not receive palivizumab. Anti-RSV NAb titers were measured using an RSV microneutralization assay. FINDINGS: Infants who received palivizumab had anti-RSV NAb titers at the end of the RSV season that persisted beyond what is expected from the pharmacokinetics of palivizumab alone. Moreover, 54% of the control infants who did not receive palivizumab and all tested adults had protective anti-RSV NAb titers. CONCLUSIONS: Based on our observations, we hypothesize that naturally acquired NAb provide additive protection, which may significantly reduce the need for additional doses of palivizumab in infants at risk of severe RSV infections.